Modern pollen signatures of the Amazon River and major tributaries - Akabane, Thomas Kenji (2019)
Part of the controversy of the ongoing debate about the paleoecology of the Amazon results from the scarcity of modern data to better elucidate the sources and processes controlling the fluvial pollen record. The Amazon River transports large amounts of pollen gathered from the several distinct environments present in the current drainage basin, but how each of these environments contribute to the pollen record remains poorly studied. In order to assess this problem, the palynological content of 36 riverbed sediment samples covering from the mouth of Içá River to the Amazon Estuary was analyzed with the support of x-ray fluorescence (XRF) analysis. The palynological analysis shows that vegetation of lowland floodplains is the main source of the pollen transported by the Amazonian rivers. Therefore, aspects of fluvial dynamics and geomorphology that control vegetation over the floodplains echo in the pollen record. The upper reaches of Amazon River and western whitewater tributaries are responsible for an abundant Cecropia contribution, reflecting an early-successional vegetation induced by high rates of lateral erosion by the rivers and a landscape dominated by scroll-bars. The middle and lower reaches exhibit a progressive increase in herbs mainly represented by Poaceae, Cyperaceae, Asteraceae, Alternanthera, maranthus, and Acalypha, related to an opening in the floodplain vegetation cover and a flatter topography occupied by lakes. Floodplain forests of whitewater rivers (várzeas) are characterized by Iriartea, Mauritia, Ilex, Pseudobombax, and Luehea, which, in consortium with high amounts of Cecropia or herbs, suggest early to late stages of succession typical of these environments. The igapó forests, on the margins of black- and clearwater rivers, are palynologically expressed by higher values of Symmeria, Sapium, Piranhea, Pouteria, Amanoa, Myrtaceae, and Alchornea, which indicate conditions of higher environmental stability and a mature forest. Contribution from the Andean Mountains and from the cerrado are clouded by the pollen production of the lowlands. Extensive anthropogenic disturbance may reflect in a local increase of Cecropia, though its influence on the overall Amazonian signature is not detected. DCA analysis shows a gradual transition of the pollen signature from the upper to the lower reaches of the Amazon River, suggesting that the hindmost pollen signature is mainly influenced by the production along the main stem. Published palynological data are contrasted and discussed in the light of the present findings.